Up to the Challenge: Adapting Pediatric Intensive Care During a Global Pandemic - Pereira, Myra; Akinkugbe, Olugbenga; Buckley, Laura; Gilfoyle, Elaine; Ibrahim, Sarah; McCradden, Melissa; Somerton, Sarah; Dryden-Palmer, Karen (Frontiers in Pediatrics, 2022)
Background: The COVID-19 pandemic has strained health systems worldwide. In our region surging numbers of critically ill adult patients demanded urgent system-wide responses. During the peak of the pandemic, our Pediatric Intensive Care Unit team redesigned existing education resources and processes of care to ensure quality care for adult patients for the first time in the hospital’s history. Aim: Describe the experiences and impacts of rapidly initiated Adult COVID-19 Program on health care providers and family members. Havelock’s Theory of Change framed the examination of Adult COVID-19 Program participant experiences and surfaced lessons learned. Methods: A quality improvement review was employed to collected health care team member and family member feedback about the program. Health care providers completed a questionnaire 10 months following implementation of the program and feedback from family members provided during the program was obtained. Havelock’s Theory of Change was used to explore trends and frame participant’s experiences. Results: PICU bedside team members and clinical leaders (n=17), adult hospital partners (n=3) and family members (n=8) participated. Health care providers describe; motivation and readiness; concern of personal safety and uncertainty experienced in the early program phases; importance of established supports and resources; use of relationships and collaboration to facilitate change; the emotional impacts of this unique experience; and opportunities for individual and team growth. An overarching theme of ‘doing our part to help’ emerged. Family members described positive impacts of family-centered interventions offered, individualized care and shock at their family member’s illness. Conclusions: The pediatric intensive care unit team rapidly adapted to provide care for adults at the peak of the pandemic. Family members expressed feeling grateful for the care their loved one received in the pediatric setting. The experience caring for adult COVID-19 patients was a source of tension, personal growth and meaning for the pediatric intensive care team. Abbreviations: Pediatric Intensive Care Unit (PICU), The Hospital for Sick Children (SickKids), Coronavirus Disease (COVID-19), family centered care (FCC), Health care providers (HCP), Interprofessional practice (IP), Registered Respiratory Therapists (RRT), extracorporeal life support (ECLS), continuous renal replacement therapy (CRRT), acute respiratory distress syndrome (ARDS), Personal Support Worker (PSW)